Face time: Effects of shyness and attention to faces on early word learning - Gert Westermann; Katherine E. Twomey; Matt Hilton (Language Development Research, 2023)
Previous research has shown that shyness affects children’s attention during the disambiguation of novel words via fast-mapping. The current study examined whether shyness also affects children’s attention when eye-gaze cues to novel word meaning are present. 20- to 26-month-old children’s (N = 31) gaze was recorded as they viewed videos in which an onscreen actor sat at a table on which one novel and two familiar objects appeared. The actor looked at and labeled one of the objects, using a novel word if the target object was novel. Overall, shyness was associated with a stronger preference for looking at the actor’s face than the object being labeled. This finding suggests that previous reports of shyer children’s reduced word learning could be explained in terms of preferential attention to faces, reducing shyer children’s opportunity to form a robust association between object and label. Overall, these findings provide new evidence that shyness exerts an effect on language development by modulating the processes by which word meanings are learned.